Multilingualism and Decoloniality in South Africa Education: French as a Gateway Language - de Oliveira, Ruth (Verbum, 2025)
This paper explores South Africa’s linguistic environment, addressing the interplay between promoting indigenous languages, the dominance of English, and the evolving role of foreign languages. The study examines how educational policies, teaching practices, and student perspectives have shaped the positioning of French, a language with a longstanding presence in the country’s schools and universities. The paper comprises three sections: an analysis of historical and policy frameworks influencing multilingual education, an exploration of student-led movements advocating decolonization, and an evaluation of French’s role in contributing to decolonial objectives. The research draws on findings from in-class fieldwork and surveys conducted at the University of Cape Town from 2020 to 2024. The conclusion highlights practical strategies that contribute to reimagining language pedagogy, promoting greater inclusivity and equity in multilingual educational systems.